Metal–Organic‐Framework‐Derived Hybrid Carbon Nanocages as a Bifunctional Electrocatalyst for Oxygen Reduction and Evolution - Liu, Shaohong; Wang, Zhiyu; Zhou, Si; Yu, Fengjiao; Yu, Mengzhou; Chiang, Chang‐Yang; Zhou, Wuzong; Zhao, Jijun; Qiu, Jieshan (Advanced materials (Weinheim), 2017)
The oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are cornerstone reactions for many renewable energy technologies. Developing cheap yet durable substitutes of precious‐metal catalysts, especially the bifunctional electrocatalysts with high activity for both ORR and OER reactions and their streamlined coupling process, are highly desirable to reduce the processing cost and complexity of renewable energy systems. Here, a facile strategy is reported for synthesizing double‐shelled hybrid nanocages with outer shells of Co‐N‐doped graphitic carbon (Co‐NGC) and inner shells of N‐doped microporous carbon (NC) by templating against core–shell metal–organic frameworks. The double‐shelled NC@Co‐NGC nanocages well integrate the high activity of Co‐NGC shells into the robust NC hollow framework with enhanced diffusion kinetics, exhibiting superior electrocatalytic properties to Pt and RuO2 as a bifunctional electrocatalyst for ORR and OER, and hold a promise as efficient air electrode catalysts in Zn–air batteries. First‐principles calculations reveal that the high catalytic activities of Co‐NGC shells are due to the synergistic electron transfer and redistribution between the Co nanoparticles, the graphitic carbon, and the doped N species. Strong yet favorable adsorption of an OOH* intermediate on the high density of uncoordinated hollow‐site C atoms with respect to the Co lattice in the Co‐NGC structure is a vital rate‐determining step to achieve excellent bifunctional electrocatalytic activity. A new strategy is developed for constructing a hollow nanostructured bifunctional oxygen reduction reaction/oxygen evolution reaction electrocatalyst with integrated high activity and fast kinetics by surface‐stabilized heterogeneous contraction of core–shell metal–organic frameworks. The resultant double‐shelled hybrid nanocages with an outer shell of mesoporous Co‐N‐doped graphitic carbon and an inner shell of microporous N‐doped carbon exhibit superior electrocatalytic performance to noble metals for oxygen reduction and evolution reactions.